2010
DOI: 10.1007/s10096-010-0915-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Klebsiella pneumoniae carrying pLVPK-derived loci and abscess formation

Abstract: Klebsiella pneumoniae-caused liver abscess (KLA) is an emerging infectious disease. However, factors other than K1-specific loci that contribute to the pathogenesis of this disease have not been identified. pLVPK is a 219,385-bp plasmid of K. pneumoniae CG43, an invasive K2 strain associated with KLA. We aimed in this study to evaluate the involvement of pLVPK in K. pneumoniae virulence and its clinical significance in abscess formation. A pLVPK-cured CG43 was isolated and its virulence was examined in a mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 38 publications
6
78
1
1
Order By: Relevance
“…pLVPK-derived terW-rmpA-iutA-silS loci are independent pathogenicity factors for abscess formation [25]. pLVPK derivatives could be extrachromosomal and carry the repA gene, or be a chromosome-integrated form [25,34]. Gene deficiency of pLVPK derivatives was found for the first time in the hvKP isolates except K1 type.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…pLVPK-derived terW-rmpA-iutA-silS loci are independent pathogenicity factors for abscess formation [25]. pLVPK derivatives could be extrachromosomal and carry the repA gene, or be a chromosome-integrated form [25,34]. Gene deficiency of pLVPK derivatives was found for the first time in the hvKP isolates except K1 type.…”
Section: Discussionmentioning
confidence: 98%
“…pneumoniae virulence determinant pLVPK is a 219,385-bp plasmid isolated from the invasive K2 strain CG43. pLVPK-derived terW-rmpA-iutA-silS loci are independent pathogenicity factors for abscess formation [25]. pLVPK derivatives could be extrachromosomal and carry the repA gene, or be a chromosome-integrated form [25,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a 219-kb pLVPK plasmid from K. pneumoniae was reported to be associated with PLA development; however, not all K. pneumoniae PLA isolates (66%, 23/35) were terW þ -iutA þ -rmpA þ -silS þ . 24 Hence, the development of K. pneumoniae liver abscesses likely results from a combination of all virulence determinants, including the phagocytic-resistant capsule and hypermucoviscosity phenotype as well as the presence of rmpA, aerobactin and other virulence-associated genes. In this study, the presence of LPS (O antigen) in DK1 maintained a level of cytokine induction level similar to that observed after high-dose inoculation of K62.…”
Section: Determination Of Neutrophil Influx Into the Liver Bymentioning
confidence: 99%
“…Reports of KLAs have also increased in Western and other Asian countries (Pope et al, 2011). Although KLA pathogenic mechanisms remain obscure, several virulence traits, including the vast amount of K1 capsular polysaccharide surrounding the bacteria surface (Fung et al, 2002), magA (Chuang et al, 2006), iron acquisition loci on pLVPK (Tang et al, 2010) and type 1 fimbriae (Struve et al, 2008(Struve et al, , 2009Stahlhut et al, 2012), have been reported. Fimbriae (also called pili) allow bacteria to attach to host cells to establish infection.…”
Section: Introductionmentioning
confidence: 99%